The implementation of collection development in the Gempita Pustaka School Library - Diaz Lana Putra; Yasmin Ananda Putri; Zulfatun Sofiyani (Berkala Ilmu Perpustakaan dan Informasi, 2025)
Introduction. School libraries serve as educational resources; nevertheless, the collection development process is commonly ignored or executed improperly. The objective of the study is to examine the Gempita Pustaka Library’s collection development process and strategic position by implementing Evans & Saponaro collection development method and SWOT analysis.